2016
DOI: 10.1007/s00425-016-2581-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel blue-light phototropic response is revealed in roots of Arabidopsis thaliana in microgravity

Abstract: Main conclusion Blue-light positive phototropism in roots is masked by gravity and revealed in conditions of microgravity. In addition, the magnitude of red-light positive phototropic curvature is correlated to the magnitude of gravity.Due to their sessile nature, plants utilize environmental cues to grow and respond to their surroundings. Two of these cues, light and gravity, play a substantial role in plant orientation and directed growth movements (tropisms). However, very little is currently known about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 60 publications
(64 reference statements)
3
40
0
Order By: Relevance
“…Our recent spaceflight study also identified an association between the red‐light phototropic response in roots and the magnitude of the gravity vector (Vandenbrink et al., ). In terms of cell growth and cell proliferation, it has been shown that when seedlings are grown in darkness, there is a lack of balance between these key plant development functions in microgravity (Matía et al., ).…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Our recent spaceflight study also identified an association between the red‐light phototropic response in roots and the magnitude of the gravity vector (Vandenbrink et al., ). In terms of cell growth and cell proliferation, it has been shown that when seedlings are grown in darkness, there is a lack of balance between these key plant development functions in microgravity (Matía et al., ).…”
mentioning
confidence: 78%
“…This observation suggests that there is an interaction between gravity and the light harvesting machinery at a genetic level. This proposed interaction between gravity and light‐related pathways may help explain the novel blue‐light phototropic response in roots of Arabidopsis grown in microgravity (Vandenbrink et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seeds were hydrated and germinated in the European Modular Cultivation System (EMCS) using the culture chambers (cassettes) previously developed for the "Tropi" experiments (Correll et al 2005). After germination, all seedlings grew in these cassettes for 4 days under continuous white light illumination supplied by an array of LED lights placed in one of the walls of the cassette and 1g gravity, provided by in the EMCS centrifuge, with the gravity vector pointing to the opposite direction of the white light source (Kiss et al 2012;Vandenbrink et al 2016). Then, seedlings grew for two additional days at the g-level of interest in six runs.…”
Section: Plant Materials and The Spaceflight Experimentsmentioning
confidence: 99%